Advances in General Anaesthesia Laser Procedures - Ball, Sharon (Operating Room Nurses Association of Canada Journal, 1992)
Lasers were introduced as surgical tools about twenty ﬁve years ago. Lasers have become the method of choice in numerous procedures and in most surgical specialties are aiding or advancing them. Many operating rooms today are equipped with one or more lasers.